Microalbuminuria in patients with preserved renal function as a risk factor for contrast-Induced acute kidney injury following invasive coronary angiography. Issue 6 (June 2016) - Meng, Haoyu; Wu, Peng; Zhao, Yingming; Xu, Zhihui; Wang, Ze-Mu; Li, Chunjian; Wang, Liansheng; Yang, Zhijian
Abstract: Objectives: To investigate the association between pre-existing microalbuminuria among patients with preserved renal function and contrast- induced acute kidney injury (AKI) following coronary angiography. Material and methods: 612 consecutive patients with preserved renal function (eGFR ≥ 60 ml/min and without macroalbuminuria) undergoing scheduled coronary angiography were stratified into microalbuminuria group (107 patients) and normal-albuminuria group (505 patients) according to the urine albumin to creatinine ratio (ACR) levels. Microalbuminuria was defined as ACR in the range of 30–300 mg/g and normal-albuminuria was defined as ACR <30 mg/g. Contrast-induced AKI was defined as a relative increase in serum creatinine (SCr) concentration of at least 25% or an absolute increase in SCr of 44.2 μmol/L within 72 h after the procedure. Results: The peak increases of SCr in microalbuminuria group were larger than those in normal-albuminuria group (10.6 ± 12.4 μmol/L vs. 4.8 ± 8.9 μmol/L，P < 0.001). The incidence of AKI was higher in patients with microalbuminuria than those with normal-albuminuria (12.1% vs. 5.0%, P = 0.005). Multivariate analysis revealed that there was an association between microalbuminuria and contrast-induced AKI risk after adjusting for confounders. Conclusion: Pre-existing microalbuminuria is associated with greater risk for AKI in patients with a preserved renal function who undergo scheduled coronary angiography.